Assessment of anxiety levels for Heathrow Airport workers after Covid-19 pandemic situation - Saif Aldeen Jaber (Pensoft Publishers, 2023)
Objectives: The worldwide spreading of Covid-19 and the serious side effects associated with have pushed the scientist to study the several challenges produced after the end of the pandemic. Emotional health problems that airport workers have progressed after Covid-19 especially due to the high contact with people from different nationalities. The purpose of this research was to examine the level of anxiety of the selected population in the association with several factors like gender, age, and other demographical factors. Materials and methods: A 214 workers from Heathrow airport with 113 females and 101 males and with age range 20-50 were selected to the study. Different demographical factors were examined to see its relation with anxiety levels that resulted from Self-Rating Anxiety Scale (SAS). SPSS 28x was used to perform different statistical analysis test on the collected data. Results: Gender, experience, salary, and education were found to affect the level of anxiety significantly with a P-value lower or equal to 0.05 at confidence interval of 95%. Males were found to exert higher percentage of anxiety symptoms when compared with female. While salary above or lower than 30000$ was found to have a similar percentages and effect. On the other hand, experience played an important role to reduce anxiety, while education have increased the risk of anxiety. Conclusion: Different authorities and work locations including airports should be taking in consideration the anxiety after the end of Covid-19 pandemic to reduce the serious clinical outcomes associated with anxiety.